Factors Linked With an Increased Risk of Death in Patients with Covid-19 - Muhammad Salman, Sarah Hameed, Husnain Hashim, Tahir Mukhtar Sayed, Asma Ashraf, Syed Imad Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to determine the factors that increase a patient’s chances of death from COVID-19. Study Design: Retrospective study Place and Duration: Medicine department of Benazir Bhutto Hospital (BBH) and Holy Family Hospital (HFH), Rawalpindi during the period from November 2021 to April 2022. Methods: Total 142 patients of both genders of confirmed coronavirus disease were included. After receiving informed written consent from each participant, detailed demographic information was obtained. This information included the participant’s age, gender, body mass index, and list of co-morbidities. Frequency of mortality and factors that increase a patient’s chances of death were recorded. SPSS 24.0 was used to analyze all data. Results: We found that 87 (61.3%) cases were males and 55 (38.7%) patients were females. Majority of the patients 53 (37.3%) had age >45 years. 65 (45.8%) patients were smokers. Severity of disease was found in 76 (53.5%) cases. There were 95 (66.9%) patients had hypertension, diabetes mellitus found in 75 (52.8%) cases, cardiovascular disease in 48 (33.8%) cases, pulmonary disease in 40 (28.2%) cases and chronic kidney disease in 34 (23.9%) cases. Among 142 patients, 27 (19.01%) patients were died. Among non-survivals, kidney dysfunction was the most common reason found in 17 cases, followed by cardiovascular and diabetes mellitus. Conclusion: We came to the conclusion that clinical risk factors for a fatal consequences associated with coronavirus include chronic chronic conditions, complications, and demographic variables. These risk factors include acute renal injury, diabetes, hypertension, heart disease, male sex, older age, current smoker, and obesity. The findings might be used to future study on the disease as well as its control and prevention. Keywords: Coronavirus, Comorbidities, Mortality, Severity